Effect of home-based cardiac rehabilitation on health related quality of life of patients following CABG surgery: A randomized clinical trial - Kobra Limoee; Shahram Molavynejad; Marziyeh Asadizaker; Amanollah Heidari; Elham Maraghi (Tehran University of Medical Sciences, 2019)
Background & Aim: Nowadays, home-based cardiac rehabilitation (HBCR) program is one of the major methods that can improve the quality of life of patients following coronary artery bypass graft surgery. The present study aimed to investigate the effect of a HBCR on the quality of life of patients following CABG. Methods & Materials: In this clinical trial, 104 inpatients at Golestan and Imam Khomeini hospitals in Ahvaz in 2017, based on permuted-block randomization were assigned to an intervention or a control group. The intervention group received four training sessions for four days at the hospital and then six sessions of home-based cardiac rehabilitation (at 2-week intervals for three months). The Mac-New quality of life questionnaire was completed by the intervention and control groups before the surgery and three months after CABG surgery. Data were analyzed using the SPSS software version 22. Results: The postoperative mean scores for quality of life subscales and for overall quality of life in the intervention group were greater compared to the control group (P<0.001). The obtained effect sizes were 1.17 for the emotional, 1.42 for the physical, and 1.91 for the social subscales and 1.67 for the overall quality of life. The Eta-squared value (0.408) indicated that the effect of the home-based cardiac rehabilitation program on the quality of life was significant (P<0.0001). Conclusion: The study findings suggest that the home-based cardiac rehabilitation program has positive effects on the various subscales of quality of life. HBCR is recommended as a cost-effective care model for all patients attending heart surgery centers. Clinical trial registry: IRCT20171114037468N1